Decoloration rates of a photomerocyanine dye as a visual probe into hydrogen bonding interactions - Ciampi, S.; Eggers, P.; Haworth, N.; Darwish, Nadim; Wagner, P.; Coote, M.; Wallace, G.; Raston, C. (The Royal Society of Chemistry, 2015)
We have developed a visual marker for the investigation of hydrogen bonding (HB) effects. The decoloration rate of a photochromic dye that incorporates a latent intra-molecular HB feature can be linked to the HB character of the media. Kinetic and thermodynamic parameters of this simple decoloration approach for HB sensing are investigated both experimentally and by high level theoretical studies. This principle has been applied for the detection of changes in the HB character of stationary and fluidic systems. A major finding is the observation of a shear-related perturbation of the balance between intra- and inter-molecular HB within a dynamic thin film.